Activation of the Absent in Melanoma 2 Inflammasome in Peripheral Blood Mononuclear Cells From Idiopathic Pulmonary Fibrosis Patients Leads to the Release of Pro-Fibrotic Mediators - Terlizzi, Michela; Molino, Antonio; Colarusso, Chiara; Donovan, Chantal; Imitazione, Pasquale; Somma, Pasquale; Aquino, Rita P.; Hansbro, Philip M.; Pinto, Aldo; Sorrentino, Rosalinda (Frontiers in Immunology, 2018)
Idiopathic pulmonary fibrosis (IPF) is a chronic fibro-proliferative disease characterized by poor prognosis, with a mean survival of ~2–3 years after definite diagnosis. The cause of IPF is still unknown but it is a heterogeneous condition in which the aberrant deposition of extracellular matrix leads to extensive lung remodeling. This remodeling is a consequence of inflammatory responses, but the mechanisms involved are poorly understood. In this study, we first analyzed a bleomycin-induced mouse model, which showed that higher expression of IL-1β, but not IL-18, was correlated to pulmonary cell infiltration and fibrosis. Then, we found that peripheral blood mononuclear cells (PBMCs) from IPF patients released IL-1α and IL-18 in a NLRP3- and calpain-independent manner after LPS±ATP stimulation. Instead, the activation of the AIM2 inflammasome induced the release of IL-1α in a caspase-1/-8 independent manner; whereas IL-18 release was caspase-1-dependent. These effects correlated with the release of the pro-fibrotic TGF-β, which was induced by AIM2 activation in a caspase-1- and TLR4-independent manner, but dependent on IL-1α. In this context, the activation of AIM2 induced the release of caspase-4 from IPF-derived PBMCs, which correlated with the mRNA levels of this caspase that was higher in IPF than in healthy PBMCs. In conclusion, our findings identify a novel molecular mechanism whereby the activation of AIM2 could lead to the activation of the non-canonical inflammasome (caspase-4-dependent), that induces the release of IL-1α responsible for the release of TGF-β from PBMCs of IPF patients.